Toddlers Help a Peer. Issue 5 (7th December 2016) - Hepach, Robert; Kante, Nadine; Tomasello, Michael
Abstract : Toddlers are remarkably prosocial toward adults, yet little is known about their helping behavior toward peers. In the present study with 18‐ and 30‐month‐old toddlers ( n  =   192, 48 dyads per age group), one child needed help reaching an object to continue a task that was engaging for both children. The object was within reach of the second child who helped significantly more often compared to a no‐need control condition. The helper also fulfilled the peer's need when the task was engaging only for the child needing help. These findings suggest that toddlers' skills and motivations of helping do not depend on having a competent and helpful recipient, such as an adult, but rather they are much more flexible and general.